Eficacia del metodo halliwick en niños con retraso psicomotor de 3 a 36 meses de edad del centro de atención especial despertar de los ángeles, 2017/2018 - Pintag Coral, Karol Daniela (2018)
The objective of this research is to demonstrate the effectiveness of the Halliwick method in the children with psychomotor retardation from 3 to 36 months of age who attend the “Despertar de lo Angeles” Attention Center in the City Riobamba. Psychomotor retardation is a pathology that affects children from the moment of birth or after this, it affects the normal development of child preventing him/her from naturally evolving to his/her surroundings, if this on time it can be attended with physical rehabilitation which will help the child of overcome his/her delay. A very efficient means of attention is the application of the Halliwick method since using the benefits of water allows the child to develop and improve motor skills. This investigation was of applied type, the population is made up by twenty-three children with psychomotor delay between the 3 to 36 months of age, which are divide in two groups of attention by the disposition of the schedule, 13 children in the morning and 10 children in the afternoon, to whom the Halliwick method was applied based on four phases and the program of ten points. The results showed that this technique is positive in the motor area since the children obtain a decrease in the months of delay, in other words the treatment was started with 2 months of delay in their psychomotor development and the result of the final evaluation showed us 1 month of delay. Concluding in the need to include the Halliwick method as part of the treatment protocol for patients with delayed psychomotor development attending the “Despertar de los Angeles” Special Attention Center.